The influence of plastic flow localization on the surface morphology of aluminum alloy specimens subjected to complex loading - Evgeniia A. Chechulina; Vladimir A. Oborin; Dmitriy S. Gribov (Fracture and Structural Integrity)
This study investigates the effects of complex (nonproportional) loading on plastic deformation in aluminum alloys (Al-6% Mg), with a focus on understanding surface morphology changes driven by the PortevinLe Chatelier effect. Mechanical tests on the deformation of thin-walled tubular specimens were carried out on an Instron 8850 two-axis servohydraulic testing system. Quantitative analysis of the lateral surface of the specimens roughness was carried out based on data obtained using a NewView 5010 interferometer-profilometer. Localized plasticity zones in a wide spectrum of spatial scales were determined using the Hurst exponent as a roughness characteristic. The results of measuring changes in the surface geometry of specimens under various programs of complex (disproportionate) loading are presented. A compact representation of data on the specimens surface relief in the form of amplitude-frequency characteristics was obtained using wavelet analysis. The results obtained can be used to assess the surface roughness of products, especially at the final stages of their manufacturing process by plastic deformation